2011
DOI: 10.1371/journal.pone.0028397
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soil Respiration to Soil Temperature and Moisture in a 50-Year-Old Oriental Arborvitae Plantation in China

Abstract: China possesses large areas of plantation forests which take up great quantities of carbon. However, studies on soil respiration in these plantation forests are rather scarce and their soil carbon flux remains an uncertainty. In this study, we used an automatic chamber system to measure soil surface flux of a 50-year-old mature plantation of Platycladus orientalis at Jiufeng Mountain, Beijing, China. Mean daily soil respiration rates (Rs) ranged from 0.09 to 4.87 µmol CO2 m−2s−1, with the highest values observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
(47 reference statements)
4
29
0
Order By: Relevance
“…Average soil respiration varied between 1.12 and 7.90 μ mol CO 2 m -2 s -1 during the growing period, typical of Chinese arborvitae (Yu et al 2011). The apparent conservation of soil respiration across treatments is consistent with the findings of Vesala et al (2005) and Campbell et al (2009), who found that soil respiration was unaffected by thinning treatments in ponderosa pine (Pinus ponderosa P. Laws.…”
Section: Soil Respirationsupporting
confidence: 82%
See 1 more Smart Citation
“…Average soil respiration varied between 1.12 and 7.90 μ mol CO 2 m -2 s -1 during the growing period, typical of Chinese arborvitae (Yu et al 2011). The apparent conservation of soil respiration across treatments is consistent with the findings of Vesala et al (2005) and Campbell et al (2009), who found that soil respiration was unaffected by thinning treatments in ponderosa pine (Pinus ponderosa P. Laws.…”
Section: Soil Respirationsupporting
confidence: 82%
“…All these will affect soil microbial respiration and root respiration. Soil temperature and moisture may explain temporal variation in soil respiration (Yu et al 2011). Increased soil temperature (Ts) and soil moisture (Ms) may also enhance root growth of remaining trees, given that there is less below-ground competition for water and nutrients (Santantonio andSantantonio 1987, Van Lear et al 2000) and photosynthetic rates (Gravatt et al 1997, Peterson et al 1997.…”
Section: Soil Respirationmentioning
confidence: 99%
“…These data are in the same range as those from other reported studies (Savage & Davidson 2001;Rey et al 2002;Kang et al 2003), except for one study in China (Yu et al 2011). For example, in the temperate broad-leaved Korean Pine forest in the Chang Bai Mountain area of China, the released CO 2 efflux was 1017 g C m 22 (Wu et al 2006).…”
Section: Annual Co 2 Effluxsupporting
confidence: 77%
“…They are the major abiotic factors controlling soil CO 2 concentrations, which often have a temperature-driven seasonal pattern, and summer rains can lead to increases in CO 2 concentrations (Yu et al 2011, Chang et al 2016. After a rainfall, CO 2 concentrations rose markedly and θ was highest in the deepest horizon.…”
Section: Vertical Distribution Of Comentioning
confidence: 99%
“…The role of soil in China's terrestrial carbon balance is a large source of this uncertainty (Piao et al 2009). Soil respiration has been determined in most districts of China (Tian et al 2010, Yu et al 2011, Pang et al 2012, but due to the limitations of measuring techniques, vertical and seasonal variations of soil CO 2 in planted forests is limited.…”
Section: Introductionmentioning
confidence: 99%